Contribution of Sos Children’s Village Project on Ending Violence Against Children in Burundi: A Case of Nyakabiga District, Burundi. - Annick Kampundu (Uganda Christian University, 2024)
This research investigates the effectiveness of child care and development programs at the SOS Children’s Village Nyakabiga in Burundi, with concentration on education, healthcare, family- based care, and community integration. This research reflects the harmonious satisfaction among respondents concerning the good quality of education, skills development, healthcare services, and the nurturing environment provided by the village's family-based care system. However, it also points of evident challenges in the part of community integration, where many children find it difficult to transition from the village into the broader community. The findings indicate that while the village is excellent in many aspects of child care, there is a need for enhanced focus on preparing children for life outside the program. recommendations such as making community integration programs stronger, facilitating additional training for caregivers and children, and establishing partnerships with local communities to make the children accustomed to interacting with the broader community. Addressing these gaps is vital for fostering leadership qualities within the children that will make the community a better place.